Risk expansion of Cr through amphibious clonal plant from polluted aquatic to terrestrial habitats - Xu Liang; Wu Xiao; Xiang Dan (Open Life Sciences, 2018)
Resource sharing between the connected ramets of clonal plants through physiological integration can increase the tolerance of plants to environmental stress. However, the role of physiological integration in the translocation of heavy-metal pollutants between different habitats receives little attention, especially in the aquatic-terrestrial ecotones. An amphibious clonal plant Alternanthera philoxeroides was used to simulate plant expansion from unpolluted soil to a chromium (Cr)-polluted water environment. Basal older ramets growing in unpolluted soil were connected or disconnected with apical younger ramets of the same fragments in polluted environments at different Cr concentrations. Harvested basal ramets were also used for decomposition tests for the loss of residual mass and release of Cr to soil. With increasing Cr concentration there was reduction in biomass of the apical ramets, especially those separated from the basal parts. Cr was detected in the basal ramets with connection to apical parts. The decomposition of plant litter from the basal ramets connected with polluted apical parts might release retained Cr to unpolluted soil. The amount and chemical forms of Cr in the plant litter changed over time. It is concluded that Cr could be transferred from polluted aquatic to unpolluted terrestrial habitats through amphibious clonal plants.